Triazine herbicide reduced the toxicity of the harmful dinoflagellate Karenia mikimotoi by impairing its photosynthetic systems - Chen, Xiang-Wu; Chen, Heng; Zhao, Hai-Ling; Li, Da-Wei; Ou, Lin-Jian (Ecotoxicology and environmental safety, 2024)
Triazine herbicides are common contaminants in coastal waters, and they are recognized as inhibitors of photosystem II, causing significant hinderance to the growth and reproduction of phytoplankton. However, the influence of these herbicides on microalgal toxin production remains unclear. This study aimed to examine this relationship by conducting a comprehensive physiological and 4D label-free quantitative proteomic analysis on the harmful dinoflagellate Karenia mikimotoi in the presence of the triazine herbicide dipropetryn. The findings demonstrated a significant decrease in photosynthetic activity and pigment content, as well as reduced levels of unsaturated fatty acids, reactive oxygen species (ROS), and hemolytic toxins in K. mikimotoi when exposed to dipropetryn. The proteomic analysis revealed a down-regulation in proteins associated with photosynthesis, ROS response, and energy metabolism, such as fatty acid biosynthesis, chlorophyll metabolism, and nitrogen metabolism. In contrast, an up-regulation of proteins related to energy-producing processes, such as fatty acid β-oxidation, glycolysis, and the tricarboxylic acid cycle, was observed. This study demonstrated that dipropetryn disrupts the photosynthetic systems of K. mikimotoi, resulting in a notable decrease in algal toxin production. These findings provide valuable insights into the underlying mechanisms of toxin production in toxigenic microalgae and explore the potential effect of herbicide pollution on harmful algal blooms in coastal environments.